(untitled) - Shafer, Scott M. (New York, 2003)
This comprehensive text will introduce students to the many operations topics and issues faced by leading service and manufacturing organizations. An emphasis is placed on new developments in the field of operations management and new information resources available, such as the Internet, while retaining a strong focus on the fundamental concepts of operations management. The goal of this text is to help students gain an understanding of what operations management involves, how it relates to other functional areas in an organization, the types of problems that are faced by operations managers, and common decision-making approaches.
Keywords: Production management